2022
DOI: 10.1042/ns20210053
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent effects of chronic exercise on cognitive flexibility but not hippocampal Bdnf in aging mice

Abstract: Cognitive impairments associated with advanced age involve alterations in the hippocampus that changes to experience throughout life. The hippocampus is critical for cognitive flexibility involved with extinction and reinstatement of conditioned fear. It is widely accepted that regular exercise can be beneficial for hippocampal function. Therefore, we asked whether chronic voluntary exercise in middle-aged mice can improve extinction and/or reinstatement of conditioned fear compared to standard housing. Eight-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 76 publications
(98 reference statements)
1
5
0
Order By: Relevance
“…A previous meta-analysis reported greater AT benefits on nonspatial memory tasks in healthy male older rodents compared to female rodents (Barha et al, 2017b). Similarly, Short et al, (2022) BDNF Val/Val mice showed an increase in ventral DCX-expressing cells compared to sedentary controls, whereas BDNF Met/Met showed minimal running and no significant increase in DCXexpressing cells compared to sedentary controls. Interestingly, the lack of an AT effect on neurogenesis in BDNF Met/Met is consistent with previous research done in younger male mice (Ieraci et al, 2016), even though these younger male mice did run as much as the younger BDNF Val/Val mice (Ieraci et al, 2016).…”
Section: At Improved Cognitive Performance In Bdnf Met/met Mice But I...mentioning
confidence: 84%
See 2 more Smart Citations
“…A previous meta-analysis reported greater AT benefits on nonspatial memory tasks in healthy male older rodents compared to female rodents (Barha et al, 2017b). Similarly, Short et al, (2022) BDNF Val/Val mice showed an increase in ventral DCX-expressing cells compared to sedentary controls, whereas BDNF Met/Met showed minimal running and no significant increase in DCXexpressing cells compared to sedentary controls. Interestingly, the lack of an AT effect on neurogenesis in BDNF Met/Met is consistent with previous research done in younger male mice (Ieraci et al, 2016), even though these younger male mice did run as much as the younger BDNF Val/Val mice (Ieraci et al, 2016).…”
Section: At Improved Cognitive Performance In Bdnf Met/met Mice But I...mentioning
confidence: 84%
“…A previous meta-analysis reported greater AT benefits on non-spatial memory tasks in healthy male older rodents compared to female rodents (Barha et al, 2017b). Similarly, Short et al, (2022) found beneficial effects of AT on cognitive flexibility in male, but not in female, middle-aged mice. It is possible that different genotypes and sexes require different amounts of AT to improve cognition, and future studies could explore longer AT interventions in the Val/Val mice.…”
Section: At Improved Cognitive Performance In Bdnf Met/met Mice But I...mentioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, an increase in plasticity-related immediate-early gene expression (c-fos) in mPFC during a similar task was reported, while its suppression was found to produce learning deficits (Morrow et al, 1999 ). However, subsequent investigations revealed the key role of the basolateral amygdala in associating sensory and shock-related inputs (Quirk and Mueller, 2008 ) and a hippocampal involvement in the reinstatement of extinguished fear (Frohardt et al, 2000 ; Short et al, 2022 ), whereas mPFC was shown to mediate primarily the consolidation of extinction. More specifically, the learning to inhibit a fear response was shown to be associated with synaptic changes in mPFC, as tested by an electric stimulation of medio-dorsal thalamus or ventral hippocampus synapses to mPFC neurons (Milad and Quirk, 2002 ; Quirk et al, 2006 ; Hugues and Garcia, 2007 ).…”
Section: Long-term Memory In Mpfc and Its Role In Rodent Behaviormentioning
confidence: 99%
“…In animals, a multidimensional high-level stimulation is modeled by the experimental paradigm of environmental enrichment [ 15 , 16 , 17 ]. However, several studies have specifically focused on the analysis of the effects of physical activity in animal models, both in physiological and pathological conditions [ 18 , 19 , 20 ]. The use of rodent-based exercise models provides a number of advantages in comparison to human studies, because of their shorter gestational period and lifespan, more numerous progenies, superior genetical and physiological homogeneity, higher control in experimental procedure choices, and the larger possibility of investigation in the nervous system [ 21 ].…”
Section: Introductionmentioning
confidence: 99%